2017
DOI: 10.7717/peerj.3026
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of EVA midsole resilience and upper shoe structure on running biomechanics: a machine learning approach

Abstract: BackgroundResilience of midsole material and the upper structure of the shoe are conceptual characteristics that can interfere in running biomechanics patterns. Artificial intelligence techniques can capture features from the entire waveform, adding new perspective for biomechanical analysis. This study tested the influence of shoe midsole resilience and upper structure on running kinematics and kinetics of non-professional runners by using feature selection, information gain, and artificial neural network ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…It is possible that mechanical factors such as tighter fixation leading to less energy loss affected performance, yet changes in proprioceptive feedback may have also influenced these outcomes. The shoe upper has the largest contact area with the foot of any other part of the shoe (Onodera et al 2017), and likely influences proprioception in addition to comfort, fit, and mechanical properties. While it is difficult to directly determine if a shoe is aiding an athlete in using their preferred movement path (Nigg et al 2018), increased proprioceptive feedback should allow for increased awareness of the athlete's segment motion, and enable more accurate and quickly executed adjustments in their movement.…”
Section: Influence Of Shoe Upper Design On Athletic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that mechanical factors such as tighter fixation leading to less energy loss affected performance, yet changes in proprioceptive feedback may have also influenced these outcomes. The shoe upper has the largest contact area with the foot of any other part of the shoe (Onodera et al 2017), and likely influences proprioception in addition to comfort, fit, and mechanical properties. While it is difficult to directly determine if a shoe is aiding an athlete in using their preferred movement path (Nigg et al 2018), increased proprioceptive feedback should allow for increased awareness of the athlete's segment motion, and enable more accurate and quickly executed adjustments in their movement.…”
Section: Influence Of Shoe Upper Design On Athletic Performancementioning
confidence: 99%
“…While the majority of shoe designs focus on the midsole, the shoe upper further facilitates the foot-to-shoe connection and provides the environment for the foot to operate. The shoe upper has the largest contact area with the foot of any other part of the shoe (Onodera et al 2017), and likely influences proprioception in addition to comfort, fit, and mechanical properties. Designers recognise the importance of fit to an athlete, but this has traditionally been defined by how the shoe last imitates an individual athlete (McPoil, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that use more advanced analysis methods are mostly focused on cyclic movements such as gait and running. It has been shown that these methods may detect age- 2 and fatigue-related 5 changes, overall variability 3 , 4 , 7 , and the effects of different equipment 6 . However, limitations such as the sheer amount of rigorous work time and the financial support it takes to collect and process the data for the further calculations make it difficult for researchers to use more advanced analysis techniques.…”
Section: Background and Summarymentioning
confidence: 99%
“…Researchers try to solve optimization problems by creating new data processing technologies [22], for example, by integration of neural nets into the system structure [23]. However, the neural net must undergo a training procedure in order to distinguish one effective solution from another, more or less effective solution.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%